Income generating NGOs in post apartheid South African townships: what role and challenge in poverty reduction? A case study of Women for Peace, Kagiso - Hortensia, Mac Courage Bih (My University, 2009)
Abstract After the apartheid regime was abolished in the early 1990s, the number of NGOs in South Africa skyrocketed. By 1997, the South African government recognized the role played by the NGOs in challenging the injustices of apartheid and addressing the needs of vulnerable communities. This led to a Non-profit Organizations Act, (No 71 of 1997) aimed at creating an enabling environment for the non-profit sector. With the abolition of apartheid and the increase in the number of NGOs, not much seems to have changed. This being the case their objectives especially of poverty reduction are not met as they are also in need. This case study thus seeks to examine the income generation projects of the NGO Women for Peace Kagiso centre. It will be looking at how the organization has helped to improve the living conditions of its beneficiaries, 30 years after its existence. It will also look at the challenges faced in running these income generating projects, as well as suggest possible measures that can help improve the situation. In order to answer the research question, I will basically implore qualitative research methods. It will involve literature review, participant observation, informal and semi-structured interviews. The sample consisted of 20 people made up of both staff members and beneficiaries.